2018
DOI: 10.1038/s41598-018-29248-2
|View full text |Cite
|
Sign up to set email alerts
|

Increased testicular blood flow maintains oxygen delivery and avoids testicular hypoxia in response to reduced oxygen content in inspired air

Abstract: Despite a long-standing assertion that mammalian testes operate near hypoxia and increased testicular temperature causes frank hypoxia, we have preliminary evidence that changes are due to hyperthermia per se. The objective was to determine how variations in inspired oxygen concentration affected testicular blood flow, oxygen delivery and extraction, testicular temperature and lactate production. Eight rams were maintained under general anesthesia, with successive decreases in oxygen concentration in inspired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Maintaining a consistent and stable supply of arterial vasculature through the supra‐main testicular artery is critical to testicular functionality (Abdelnaby et al., 2021b; Herwig et al., 2004). Several reports on humans (Battaglia et al., 2000; Rizzotto et al, 2018), stallions (Bollwein et al., 2008), donkeys (Abdelnaby et al., 2021b), camels (Kutzler et al., 2011) and Shiba bucks (Samir et al., 2015) have shown a link between plasma testosterone levels, semen quality and testicular haemodynamics. Elevation of the main testicular artery blood flow waveform pattern could result in a marked elevation in male fertility through a direct effect on the spermatogenesis process (Rizzoto et al., 2018; Velasco & Ruiz, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Maintaining a consistent and stable supply of arterial vasculature through the supra‐main testicular artery is critical to testicular functionality (Abdelnaby et al., 2021b; Herwig et al., 2004). Several reports on humans (Battaglia et al., 2000; Rizzotto et al, 2018), stallions (Bollwein et al., 2008), donkeys (Abdelnaby et al., 2021b), camels (Kutzler et al., 2011) and Shiba bucks (Samir et al., 2015) have shown a link between plasma testosterone levels, semen quality and testicular haemodynamics. Elevation of the main testicular artery blood flow waveform pattern could result in a marked elevation in male fertility through a direct effect on the spermatogenesis process (Rizzoto et al., 2018; Velasco & Ruiz, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Several reports on humans (Battaglia et al., 2000; Rizzotto et al, 2018), stallions (Bollwein et al., 2008), donkeys (Abdelnaby et al., 2021b), camels (Kutzler et al., 2011) and Shiba bucks (Samir et al., 2015) have shown a link between plasma testosterone levels, semen quality and testicular haemodynamics. Elevation of the main testicular artery blood flow waveform pattern could result in a marked elevation in male fertility through a direct effect on the spermatogenesis process (Rizzoto et al., 2018; Velasco & Ruiz, 2021). Any declination in the main spectral wave of the testicular artery causes ischaemic changes that negatively affect the spermatogenesis process (Tarhan et al., 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study showed that the basic structures of testicular and epididymal arteries and microarteries in Tibetan Sheep were similar to those in other mammals (Polguj et al., 2011; Polguj et al., 2015). Studies have shown that the differences in the morphology of the testicular artery protect sperm production and movement, with the coils facilitating vascular elongation or contraction, reduction of vascular pressure and regulation of blood flow (Chubb & Desjardins, 1982; Rizzoto et al., 2018). These studies found that the internal lobular artery, centripetal artery and centrifugal artery in the testicles were more abundant, indicating that the blood supply in the testicles was more abundant and conducive to spermatogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Due to relatively low oxygen concentrations in seminiferous tubules, physiological control of blood flow is pivotal for physiological testicular function. For example, exposing the testis to acute hypoxic conditions (13% oxygen in inspired air) increased testicular blood flow and oxygen uptake, with no indications of hypoxia (Rizzoto et al., 2018). Since testicular blood flow profoundly affects testicular function, maintaining an adequate arterial blood supply is critical.…”
Section: Introductionmentioning
confidence: 99%